An experimental investigation of a modified-halftone encoded gray scale image compression system for slow-scan videoteleconferencing - Jose, Antonio (Animo Repository, 1994)
The study involves the implementation of an algorithm for compression of image data using a combination of bit-plane coding and frame-replenishment coding. A method is used here to extend the gray scale display capability of a VGA monitor from 16 to 61 levels. Experiments are then performed to determine the compression capability of the algorithm and the quality of the images produced using subjective and quantitative measures. The target application considered by the study is slow-scan videoteleconferencing.